A társadalomtudományok rendszere és a társadalomelmélet - Molnár Gábor (Közép-európai közlemények, 2020)
The paper compares three historical reconstructions of the differentiation and institutionalization process of the main modern social science disciplines during the 19th and early 20th centuries, offered by Immanuel Wallerstein (and the Gulbenkian Commission), Eric R. Wolf, and Jürgen Habermas. All three regards it as a process based on the social construction of distinctions between respective domains, most importantly – in the case of economics, political science and sociology – a separation of the state, the market and civil society. However, Wolf and, somewhat less unambiguously, Wallerstein take a realist stance in rejecting this separation as artificial. Habermas, on the other hand, partially accepts it, based on his theory of the uncoupling of system and lifeworld. The second part of the paper considers the issue of social science systematics from the perspective of the (more or less systems theory oriented) social theories of Talcott Parsons, NiklasLuhmann and Habermas.It is argues that creating social theory as some kind of metadisciplinary social science provides these thinkers a unifying point of view, from which disciplinarized knowledge may prove to be, instead of a shortcoming to be overcome or a liability to get rid of, a promising resource.This conception of a metadisciplinary social theory legitimizes Parsons’, Luhmann’sandHabermas’ practice of using a very ample empirical basis in their theory building. That is why, in the author’s opinion, we should incorporate it into the program of „opening the social sciences” devised by the Gulbenkian Commission.